Absorption of NPK in Leaf and Bulb of Onion (Allium cepa L) under Varying Water Quality and Nitrogen Fertigation: NPK Content in onion under water quality and N fertigation - Sharma, Avni; N Gupta; A Malik; KS Sekhon (Journal of Soil Salinity and Water Quality, 2025)
An experiment was conducted in randomized complete block design to study the impact of varying water qualities viz. canal water (CW), poor quality saline tube well water (TW) and alternate CW and TW (CW-TW) and three N fertigation levels [ 100% (N100), 120% (N120) and 140% (N140) of recommended dose of N (RDN)] under surface drip irrigation (DI) and with 120% RDN under conventional irrigation (CI) on absorption of NPK in leaf and bulb of onion (Allium cepa L.) at Jodhpur Farm of PAU Regional Research Station, Bathinda. The onion plants were divided into leaves and bulb at 60 days after transplanting (DAT). With the increase in irrigation water salinity a decrease in N, P and K content and nutrient uptake in both plant parts was observed. CW and TW under DI, recorded the highest and the lowest macronutrient content and uptake in leaves and bulb of onion, whereas CW-TW registered the intermediate values for these macronutrients. Highest fertigation of 140 % RDN under DI recorded the maximum content of N, P and K in both the plant parts.CI held the significantly lower N, P and K content and uptake in both plant parts with CW, TW and CW-TW than DI at the same 120% RDN. It is concluded that assimilation of NPK in both leaves and bulb at 60 DAT was higher in DI than CI at 120% RDN, irrespective of water quality. However, cyclic use of good quality canal water and poor quality saline tube well water (CW-TW) under DI with 20% higher N fertigation than the recommended absorbed higher NPK in comparison with TW, though eventually lower than CW.